CAF combination chemotherapy in breast cancer patients with liver metastasis - Al Rawak, Khudair J. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: management modalities for liver metastasis from primary breast cancer are evolving steadily but systemic chemotherapy remains the mainstay of treatment. Patients and methods: 30 patients with breast carcinoma and liver metastasis managed at (Baghdad teaching hospital) during the period from Jan. 2005 to Jan. 2007. Results: 16 patients showed response to chemotherapy. 20% complete response was found and 33% showed partial response 57% went into progressive disease. The duration of response lasted for less than six months in 4 patients and more than six months in two patients. Conclusion: chemotherapy remains the mainstay of treatment of liver metastasis but new modalities of treatment add much for chemotherapy if used in combination.